Liquid low-level radioactive wastes treatment by using hydrophobized track-etched membranes. (January 2020) - Zdorovets, M.V.; Yeszhanov, A.B.; Korolkov, I.V.; Güven, O.; Dosmagambetova, S.S.; Shlimas, D.I.; Zhatkanbayeva, Zh.K.; Zhidkov, I.S.; Kharkin, P.V.; Gluchshenko, V.N.; Zheltov, D.A.; Khlebnikov, N.А.; et al.
Abstract: In this paper, we present the results of liquid low-level radioactive wastes (LLLRW) treatment by direct contact membrane distillation (DCMD) using polyethylene terephthalate (PET) track-etched membranes (TeMs). PET TeMs were modified by styrene and triethoxyvinylsilane (TEVS) using UV-induced grafting. Modification led to increase in the contact angle to 99° of PET TeMs (pore size from 150 to 300 nm). Hydrophobic PET TeMs were investigated by X-ray photoelectron spectroscopy (XPS), Fourier-transform infrared spectroscopy (FTIR), goniometric analysis, gas permeability test, liquid entry presser (LEP) analysis and scanning electron microscope (SEM). Prepared membranes were tested in treatment of LLLRW by DCMD. The influence of pore size on water flux and rejection degree was studied. Rejection degree was evaluated by conductometry and atomic emission methods. Decontamination factors (evaluated by gamma-ray spectroscopy) for 60 Co, 137 Cs, and 241 Am were found to be 85, 1900 and 5 respectively. In most cases degree of rejection of Cs, Mo, Sr, Sb, Al, Ca, Fe, K, Mg and Na ions were more than 90% and close to 100%. The use of TeMs with a narrow pores size distribution and without tortuous channels allowed us to achieve better purification from radioactive wastes in comparison with hollow-fiber membranes. Highlights: PET track-etched membranes were hydrophobized by photografting of TEVS and styrene. Influence of parameters on grafting degree were studied, optimal condition was found. Membranes were characterized by FTIR, SEM-EDX, contact angle, LEP. Prepared membranes were tested in membrane distillation of radioactive wastes.